2010
DOI: 10.1590/s0100-83582010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Interferência de caruru-de-mancha sobre características de crescimento e produção da beterraba

Abstract: Interferência de caruru-de-mancha sobre características ... RESUMO -A beterraba (Beta vulgaris), importante hortaliça cultivada no Brasil, é muito suscetível à interferência de plantas daninhas, sendo Amaranthus viridis uma das principais espécies encontradas em áreas de horticultura. O objetivo deste trabalho foi estudar a resposta da beterraba à competição com diferentes densidades de A. viridis, por meio da avaliação de características de crescimento e produção da cultura. Um experimento em caixas, com área… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The interception of solar radiation by weeds, preventing the passage of light into the crop, depends on the composition, density, and distribution of these plants (Pitelli, 2014). Marcolini et al (2010) verified that the beet crop was very sensitive to the interference imposed by A. viridis plants, showing a significant reduction in leaf area, number of leaves, dry mass of leaves, mean root diameter, and fresh mass of roots even at low densities of weed populations.…”
Section: Inter-specific Interference Between Pepper and A Viridismentioning
confidence: 70%
See 2 more Smart Citations
“…The interception of solar radiation by weeds, preventing the passage of light into the crop, depends on the composition, density, and distribution of these plants (Pitelli, 2014). Marcolini et al (2010) verified that the beet crop was very sensitive to the interference imposed by A. viridis plants, showing a significant reduction in leaf area, number of leaves, dry mass of leaves, mean root diameter, and fresh mass of roots even at low densities of weed populations.…”
Section: Inter-specific Interference Between Pepper and A Viridismentioning
confidence: 70%
“…Amaranthus is one of the major genera of weeds infesting peppers in Mexico and Canada (Amador-Ramirez, 2002;Robinson et al, 2008). It is also one of the most important weeds for various bean cropping areas (Barroso et al, 2012) and vegetable cultivation sites (Marcolini et al, 2010). Barroso et al (2012), in studies of inter-specific competition between beans and A. viridis, reported that the presence of weed decreased yield by 26%, negatively affecting the crop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A beterraba (Beta vulgaris L.), importante hortaliça cultivada no Brasil, teve sua produção aumentada nos últimos anos principalmente em função da comercialização de seus produtos minimamente processados. Dentre seus vários componentes de interesse nutricional pode-se destacar a presença de vitaminas A, B1, B2, B5 e C além de minerais como cálcio, ferro, potássio, sódio e zinco (MARCOLINI et al, 2010). Dentre as regiões produtoras de beterraba do Brasil, Revista Brasileira de Tecnologia Agroindustrial destacam-se os Estados de São Paulo, Minas Gerais e Rio Grande do Sul, que juntos somam 42 % da produção nacional desta hortaliça tuberosa.…”
Section: Revista Brasileira De Tecnologia Agroindustrialunclassified
“…In Brazil, beetroot, is one of the most ten vegetables grown and consumed (Marcolini et al, 2010). It is a nutritional demanding crop, requiring fertilization program capable of supplying its consumption requirement in the crop.…”
Section: Introductionmentioning
confidence: 99%